Development of a Teaching Module for Classification of Living Things Integrated with the Qur'an and Hadith Based on the Religious Character of MTs Grade VII Students - Laela Sari, Putri; Windyariani, Sistiana (Jurnal Report of Biological Education, 2025)
Background: This study aims to develop a teaching module for the classification of living things integrated with the Qur'an and Hadith based on the religious character of seventh-grade MTs students. Method: The method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 32 seventh-grade students of MTs Al-Ma'tuq Sukabumi. The validation instrument involved material experts, media experts, integration experts, and educator practicality, and the effectiveness test was conducted through a posttest and questionnaire. The validation results showed that the module was in the very valid category (score 83%–91%). Results: Meanwhile, the implementation results showed that the module was able to significantly improve students' religious character, with an average score of above 91% for each indicator. In addition, student and teacher responses to the use of the module were also very good. Conclusion: This study concluded that the developed module was proven to be valid, practical, and effective in training students' religious character and received positive responses from educators and students. Keywords : Integration of the Qur'an and Hadith; Classification of Living Things; Learning Module; ADDIE Model;